Translation Techniques on Kaseysaus’s Webtoon Canvas Entitled “The Fish that Loved the Bird” - Aprilia, Tyas; Purwandari, Gigih Ariastuti; Mariasari, Septi (Jurnal Vokasia, 2022)
Webtoon Canvas is a digital platform used to read digital comics or webcomics. Webtoon Canvas is provided for indie comic creators who can publish their work without having to be contracted comic creators. One example of a Webtoon Canvas is “The Fish That Loved The Bird” by KaseySaus, with the fantasy-romance genre published in 2017. This webcomic tells the story of two teenagers from two different races, the Avians and the Merpeople. There were nine translation techniques in translating the Webtoon Canvas entitled “The Fish That Loved The Bird.” The techniques that used were Transfer Techniques, Functional Equivalent Techniques, Synonyms Techniques, Continuous Translation Techniques, Conversion or Transposition Techniques, Modulation Techniques, Compensation Techniques, Subtraction-Development Techniques, and Note-Addition-Information Techniques. Constraints in the translation process were difficulties in determining the translation object, carrying out job training that were adjusted to the implementation schedule, and finding the appropriate equivalent of words in Indonesian. The solution waspaid attention during observations to find the suitable translation object for the target reader, improve time management, and improve the ability to read dictionaries and learn idiom words. Translation techniques assist in the translation process to produce translations that were by the equivalent words and daily conversation in the target language. The obstacles that were found become learning media to improve the translation ability.The applied solution helps in the translating process and completing the translation object.